JQuery UI 1.7 : the user interface library for jQuery : build highly interactive web applications with ready-to-use widgets from the jQuery user interface library /: the user interface library for jQuery : build highly interactive web applications with ready-to-use widgets from the jQuery user interface library. (©2009) - Unknown
No abstract available